Long-term internal erosion mechanism of organic matter in sediments solidified by cement, lime, and metakaolin - Wang, Hongxing; Zhang, Dizhi; Wu, Shangwei; Jing, Xiaofei; Liu, Kehui; Ren, Lingyan (Frontiers in Earth Science, 2023)
In applications of stabilized/solidified (S/S) sediments, the organic matters inside original sediments will decompose and release fulvic acid (FA) and humic acid (HA) gradually, which may reduce the durability of the S/S sediments. It is critical to reveal this long-term internal erosion mechanism to promote durability of S/S sediments. Thus, S/S sediments solidified by commonly used cement, lime and metakaolin were first prepared in laboratory. Reasonable proportioning of the additives was determined through orthogonal tests. Then, unconfined compression strength tests, measurements of organic environment indexes and chemical environment indexes, and scanning electron microscopy analysis were conducted at different curing periods of S/S sediments to explore the erosion mechanism. Consequently, the following results and conclusions are obtained: (1) microstructure of S/S sediments is composed of sediment aggregate core, hydrated calcium silicate (CSH) shell covering the core, and calcium hydroxide (CH) submerged in the CSH shell; (2) HA and FA are released gradually from organic matter decompositions inside the core, and consumed by neutralization reactions with solidification products;(3) the dissipation process of organic matters and induced damage process of S/S sediments can be partitioned into 3 stages: in the first stage, HA and FA jointly neutralize with solidification products inside the CSH shell, CSH shell is eroded gradually, and S/S sediments lose strength gradually; in the second stage, the neutralization reactions are still inside the CSH shell, but only between FA (but not HA) and solidification products, CSH shell breaks down at the end of this stage, but S/S sediments do not lose much strength until the end point; in the third stage, the neutralization reactions take place outside the CSH shell between HA (but not FA) and solidification products, and S/S sediments lose strength dramatically. It is also concluded that: HA rather than FA is more likely to neutralize with solidification products in higher alkaline environment; HA is much stronger in chemical affinity with Ca2+ ions than FA; HA controls the strength loss of S/S sediments, while FA controls the working status of HA; the developments of HA contents and Ca2+ ion concentrations reflect the strength loss of S/S sediments.